STRATEGIC PRIORITIES OF SOCIO-ECONOMIC DEVELOPMENT OF UKRAINE IN THE CONTEXT OF GLOBAL CHALLENGES - Sokur, Maryna (Social Economics, 2020)
Globalized challenges of the world economy have created an objective need for Ukraine to develop in the face of the country’s lack of preparedness for global competition and integration. The development of the economy of Ukraine in the context of globalization is taking place in a context of incomplete systemic socioeconomic and political transformation and poses problems related to the optimal integration of the economy of the country into the global economy. At the same time, the impact of globalization processes calls for new theoretical approaches to justify the structural transformation of a country’s economic development model. The directions of globalization for national economies are quite complex and contradictory. Globalization is deepening specialization and cooperation globally and the international division of labor. International competition stimulates the development of innovative processes and state-of-the-art technologies through technology transfer among countries of the world. The current model of development in Ukraine is characterized by significant deformations of the economy: fragmentation of technological space, excessive social differentiation, increased poverty, unemployment and a reduction in the population, The Russian Federation is a country with many countries, which have been affected by human-made environmental degradation and overload, the shrinking of the domestic market and the national economy, the rise of the shadow economy, the rise of corruption, etc. All this points to a structural imbalance in the Ukrainian economy. The further intensification of globalization processes will exacerbate the problem of national identity, The solution of which many countries see the strengthening of State influence on international economic cooperation through the introduction of protectionist measures in the areas of trade, migration and investment, that in turn will contribute to the strengthening of geo-economic and geopolitical tensions in the world. In this context, there is a need to establish new principles for world economic stabilization and development.